Drug convertarule. Issue 6372 (9th April 1983) - Brodie, M J; Robson, A; Murray, T
Abstract : A convenient pocket ruler has been developed that allows conversion between metric and molar measurements of many of the drugs for which therapeutic monitoring in the circulation is commonly used. The ruler also gives information to the clinician on suggested therapeutic ranges for the incorporated drugs.